Website Usage Analysis as a Provider of Information and Promotions - Agustina, Merry; Kurniawan, M. Rizky; Ariantoro, Tri Rizqi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Paradigm changes are also occurring in the field of marketing which is shifting from a selling and marketing concept to a holistic marketing concept which is caused by rapid changes in the market and its supporting technology with the Internet as the main pillar. Based on data from https://databoks.katadata.co.id/ The Data Reportal report noted that there were 4.95 billion internet users in January 2022. This number increased 4% from 4.76 billion people in January 2021. As of January 2022, internet users in Indonesia it reached 204.7 million. This number covers 73.7% of Indonesia's total population. One of the sophisticated Internet facilities that is widely used by business people as a means to promote their products is through websites. Facilities that can change the existence of a business into unlimited information that can be accessed by people in various corners of the world without having to spend large amounts of capital are a promising offer from the existence of the Internet today. The results of this research explain the path coefficient (β) and t-test, all hypotheses that influence User Satisfaction are declared accepted. Then, referring to the results of the choices in the questionnaire, the Usability Quality (USA) variable has a fairly high influence on User Satisfaction compared to other variables. This is related to the quality of the website, which is attractive in terms of user interface and ease of operation. Of course, this creates a positive experience for users when accessing the Mitra10 website. It is hoped that Mitra10 can improve the quality of the website in terms of usability and service interaction quality because these variables have a significant positive influence on user satisfaction of the Tokopedia website. One way to increase usability is to improve the appearance of the website so that the menus on the website are easier to find. Mitra10 is expected to focus more on the service interaction side because it has an influence on high user satisfaction. If service interaction is improved, user satisfaction will also increase significantly.